The Effect of Tax Rates on Tax Compliance in International Joint Venture: A Systematic Literature Review - Putri, Mareta; Sihombing, Belandina Anita Sere; Mukhtaruddin, Mukhtaruddin (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This review systematically analyzes the literature on the effect of tax rates on tax compliance in International Joint Ventures. Of the 19 studies reviewed, 16 studies show that tax rates have a positive influence on International Joint Venture compliance, by increasing transparency, investment incentives, and financial stability. Meanwhile, the remaining 3 studies suggest that rate uncertainty can have a negative impact on joint venture compliance, especially in countries with unstable tax regulations. The results of this study provide a deeper understanding of the role of taxation in providing a reference for investors and policymakers in designing tax policies that are more conducive to cross-border investment.